The Dominant Type of Planktons Consumed by Climbing Perch Larvae (Anabas Testudineus Bloch) in Danau Bangkau - Rukmini Rukmini (Center for Journal Management and Publication, 2018)
This research aimed to analyze dominant type of plankton is consumed by Climbing Perch fish larvae in relation to the abundance of plankton in the waters. The location of this research in waters Danau Bangkau. The field observations were taken by randomly purposive sampling. The results showed that dominant type of plankton eaten by climbing perch larva namely : age 3 to 11 days of taking Coconeis sp, Mougeotia sp, and Mougeotia sp. Age of 11 to 15 days of taking Coconeis sp, Brachionus sp, and Keratella sp. Age of 15-19 days of taking Navicula sp, Diatoma sp, Brachionus sp, and Keratella sp. Age of 19 to 23 days of taking Navicula sp, Brachionus sp, and Keratella sp. Age of 23 to27 days of taking Brachionus sp. and Keratella sp. Age of 27 to 31 days of taking Navicula sp, Brachionus sp, and Keratella sp.